FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI CABAI MERAH KERITING (CAPSICUM ANNUM L) DI KECAMATAN MOROTAI SELATAN KABUPATEN PULAU MOROTAI - Diningsih, Nia Komaladewi; Basuki, Natal; Kaddas, Fatmawati; Mahmud, Haris (Universitas Muhammadiyah Sidenreng Rappang, 2024)
Chili Seeds (Capsicum Annum L.) are one of vegetables commodities which is cultivated by farmers in Indonesia, because they have high selling price. Chili Seeds are one of vegetables commodities for improving farmers welfare. The purpose of this research is for analysis what the factors influence of production Chili Seeds (Capsicum Annum L.) in South Morotai Sub-District, Morotai Island District, by determining the sample using a saturated sample. The results of this research show that the factors influence of production Chili Seeds in South Morotai District the factors that simultaneously influence the production of in South Morotai District are land, seeds, fertilizer, pesticides and labor. This is very real (significant) in increasing the production of Chili Seeds. Partially, namely the pesticide factor with a significant value of 0.023 < 0.05 and the labor factor with a significant value of 0.013 < 0.05.